Short-term neurocognitive and symptomatic outcomes following mild traumatic brain injury: A prospective multi-centre observational cohort study. (23rd February 2017) - Bloom, Benjamin M.; Kinsella, Kathryn; Pott, Jason; Patel, Hiren C.; Harris, Tim; Lecky, Fiona; Pearse, Rupert
ABSTRACT: Objective : To determine the short-term cognitive and symptomatic outcome following mild traumatic brain injury. Methods : Setting: Emergency Departments of two UK tertiary referral hospitals. Participants: Adult patients presenting to the Emergency Departments of the Royal London Hospital and Salford Royal Hospital with suspected traumatic brain injury within 24 hours and Glasgow Coma Score > 8. A non-TBI comparison group included adult patients with no head or neck injury. Design: Prospective multi-centre cohort study. Main measures: The Standardized Assessment of Concussion (SAC), the Concussion Symptom Inventory (CSI) and total number of symptoms, measured at baseline and 72 hours. Results : This study enrolled 189 patients with and 51 patients without TBI. Patients with TBI had marked cognitive impairment which persisted at 72 hours (SAC score at baseline = 25 [23–27] vs 72 hours = 25 [22–27]; p = 0.1). Patients with TBI had persistent high symptom severity, although this had decreased at 72 hours (CSI score at baseline = 9 [4–22] vs 72 hours = 5 [1–19], p = 0.002). A similar pattern was observed with the total number of symptoms (baseline = 4 [2–8] vs 72 hours = 0 [0–4]; p < 0.001). Patients with TBI had worse neurocognitive function, higher overall symptom severity and higher total number of symptoms compared with patients without TBI. Patients without TBI' neurocognitive function and symptom severity remained constant, but the number of symptoms reduced between baseline and 72 hours. Conclusion : There is a cognitive deficit and symptom burden in patients with mild TBI presenting to the Emergency Department which persists at 72 hours.